Impact of close proximity pulse width modulation switching events on electric machine terminal voltages - David A. Hewitt; Shubham Sundeep; Antonio Griffo; Jiabin Wang (IET Electric Power Applications)
Abstract Electric machines form an essential part of a wide range of modern systems. When speed control is required, the use of pulse width modulation‐based inverters is generally the solution of choice. It is also usual to connect the machine to the inverter using a cable. The combination of these three elements produces the potential for voltages which exceed the dc link voltage to occur at the machine terminals. Methods for predicting the terminal voltage exist; however, these methods assume that the pulses applied to the system can be considered as isolated, discrete events. The authors highlight an issue with this assumption. When a switching event occurs, it will cause a voltage disturbance in the unswitched phases of the system due to the mutual coupling between the phases. If a second switching event occurs within a short time of this event the resultant voltage will interact with the previous switching event resulting in a higher terminal voltage than would be the case for an isolated event. This effect can be problematic for insulation design if it is not considered. This issue is demonstrated, with the worst‐case scenarios identified and potential methods of reducing terminal voltage being proposed.